Development of Early Childhood Education Theory Modules Literacy-Based: Strategies to Improve Student Cognitive - Yapandi Yapandi; Fitri Jayanti (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
This research produced a product in the form of a module on early childhood education theory to improve student cognitive. The module designed is a source of literacy for Early Childhood Islamic Education (PIAUD) students. The research that will be carried out using Research & Development (R & D) research for the subjects of this study is 31 PIAUD IAIN Pontianak students consisting of semester 5 in the 2021/2022 academic year. The author collected data from February to April 2022 using interview techniques, observations, and student activities in the PIAUD IAIN Pontianak study program. In addition, to support the data collected, the author also carried out documentation in the form of study program archives and PIAUD IAIN Pontianak student activities. The data analysis that the author did was a sociological analysis analysing observations in the PIAUD IAIN Pontianak study program. This study showed that the modules were declared suitable for use with assessment results from material experts 84.5% and media experts with an average value of 100%.